An efficient fluctuating charge model for transition metal complexes. - Comba, Peter; Martin, Bodo; Sanyal, Avik (Journal of computational chemistry, 2013)
Europe PMC is an archive of life sciences journal literature., An efficient fluctuating charge model for transition metal complexes.
Gesehen am 04.05.2021